A RARE CASE OF PSEUDOPHEOCHROMOCYTOMA WITH PANIC ATTACK WITHOUT AGORAPHOBIA – A CASE REPORT - Amran, Iskandar Mirza (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Pseudopheochromocytoma is a rare but often disabling syndrome comprised of paroxysmal severe hypertension and symptoms of catecholamine excess including anxiety, tremors, sweating and palpitations. It is a diagnosis of exclusion. There is considerable overlap between pseudopheochromocytoma and panic disorder. How psychological factors influence the severe and acute rise in blood pressure seen in patients with pseudopheochromocytoma is unknown. CASE A case of a young hypertensive patient diagnosed at the age of 26 years old without proper follow up is presented. He arrived at a tertiary hospital with symptoms of paroxysm and chest pain and was diagnosed as a case of ischemic stroke with uncontrolled hypertension.. 24-hour urine catecholamine screening showed a mild rise of norepinephrine with normal epinephrine and dopamine levels. We proceeded with a 24-hour urine normetanephrine screening which revealed mildly elevated normetanephrine and a normal metanephrine level. Repeat testing showed normal evels of both normetanephrine and methanephrine. Multiphasic adrenal CT was unremarkable except for an incidental finding of a tiny simple renal cyst. Due to recurrent chest pain, multi-slice cardiac CT was done which showed normal findings. Despite the maximal dosages of an alpha- and beta-blocker, blood pressure remained uncontrolled. Addition of spironolactone showed no benefit. Patient was referred to the psychiatric department for evaluation. He was diagnosed with panic attack without agoraphobia and was started with alprazolam for symptom control. CONCLUSION While the current study represents an important addition to the limited literature on pseudopheochromocytoma, its mechanism has yet to be fully explained and a specific diagnostic test has not been identified. The findings support the use of alpha- and beta-blockade without any other possible treatment options for now. With such scarce data, optimal treatment for pseudopheochromocytoma remains challenging.